Can we improve service efficiency in CAMHS using the CAPA approach without reducing treatment effectiveness?. (June 2016) - Fuggle, Peter; McHugh, Annie; Gore, Lucy; Dixon, Emily; Curran, Daniel; Cutinha, Darren
Health-care systems are under increasing pressure to deliver more care with similar or even less resources and there is concern that this may be achieved at the cost of reduced clinical effectiveness. In Child and Adolescent Mental Health Services (CAMHS), the Choice and Partnership Approach (CAPA) has been widely adopted as a way of increasing the efficient use of limited service resources. Some evaluations have reported increased patient flow and reduced waiting times, but it remains unknown whether such changes have been achieved at a cost of clinical effectiveness. This article describes a pragmatic multi-method evaluation of a CAMHS service reporting service outcomes (client satisfaction, waiting times, and patient flow) and clinical outcomes (clinician-rated clinical outcomes and goals achieved by families). Results showed improved service outcomes (high levels of client satisfaction and reduced waiting times) and an increase in patient flow (49 cases increased to 72 cases over an equivalent time period). Clinical outcomes showed no reduction in effectiveness and a significant improvement against the agreed goals of the intervention. The evaluation suggested that a well-structured goal-focused patient flow system may improve services by increasing patient flow while maintaining high satisfaction levels, without negatively impacting clinical effectiveness.